Methods of CPU cooling - E. I. Strashko; M. V. Shamarov; R. A. Zhlobo (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Modern methods of cooling the central processor associated with the development and use of various refrigerants and coolants in various types of personal computers are considered.Method. A significant scientific and innovative challenge in CPU cooling today is the development of cooling methods that are most efficient for server hardware while reducing energy consumption noticeably. One way to address this challenge is the assembly and use of installations capable of preventing equipment overheating and its disposal due to their functionality.Result. The main types of cooling devices are presented, their advantages and disadvantages are indicated, operation diagrams of these installations are given, as well as the results of a comparative analysis of their operation. The circuits of the Peltier element and the Seebeck effect are described; efficiency of both conventional air coolers and complex liquid cooling systems.Conclusion. The choice of CPU cooling method depends on the user's needs and processor specifications. The effectiveness of a cooling system depends on the quality of the components and their compatibility with the specific system. Liquid cooling remains the most effective and promising method for cooling central processors in modern high-performance computers.